Topographical Distribution and Spatial Interactions of Innate and Semi-Innate Immune Cells in Pancreatic and Other Periampullary Adenocarcinoma - Lundgren, Sebastian; Micke, Patrick; Elebro, Jacob; Heby, Margareta; Hrynchyk, Ina; Nodin, Björn; Leandersson, Karin; Mezheyeuski, Artur; Jirström, Karin (Frontiers in Immunology, 2020)
Background: The clinical management of pancreatic and other periampullary neoplasms remains challenging. In contrast to other cancer types, immunotherapies are largely ineffective, and the reason for the deprived immune response and the immune inhibiting cellular composition is only fragmentarily understood. The aim of this study was to comprehensively map the abundance, topographic distribution and spatial interaction of innate and innate-like immune cells in the tumour microenvironment of periampullary adenocarcinoma. Methods: Multiplexed immunofluorescent imaging was performed on tissue microarrays with tumours from a consecutive cohort of 175 patients with resected periampullary adenocarcinoma. To obtain a detailed spatial analysis of immune cell infiltration, two multiplex immune panels including antibodies against CD3, NKp46, CD56, CD68, CD163 and CD1a, CD208, CD123, CD15, CD68 and pan-cytokeratin were applied. Results: The infiltration of natural killer (NK) cells and NK T-cells (NKT) was lower in malignant compared to benign tissue. NKT cells were more abundant in intestinal type compared to pancreatobiliary type tumours, and were associated with more favourable clinicopathological features and a prolonged survival. The interaction of NKp46+ NKT cells with macrophages was also associated with a prolonged survival. Conclusions: This study provides a comprehensive map of the innate immune landscape in periampullary adenocarcinoma. NK cells, and even more so NKT cells, are revealed to be central players in the local immune response in a clinically relevant context.